Electron Transfer: Ultrafast Plasmonic Hot Electron Transfer in Au Nanoantenna/MoS2 Heterostructures (Adv. Funct. Mater. 35/2016). (September 2016) - Yu, Ying; Ji, Ziheng; Zu, Shuai; Du, Bowen; Kang, Yimin; Li, Ziwei; Zhou, Zhangkai; Shi, Kebin; Fang, Zheyu
Abstract : On page 6394, Z. Y. Fang and co‐workers apply a femtosecond pumping‐probe technique to measure electron transfer of synthesized AU nanoantenna (NA)/MoS2 heterostructures. The results indicate an ultrafast optical response time and a high cutoff frequency for devices based on this heterostructure. Combining the optoelectric properties of MoS2 with the plasmonic properties of Au NAs holds great promise for photodetectors and photovoltaics.